Saul Pett papers - Pett, Saul, 1918-1993.
Correspondence, notebooks, stories file, legal documents, and photographs documenting Pett's career with the Associated Press. Includes interview notes and articles about James Abourezk, Jimmy Carter, William T. Coleman, Gerald R. Ford, Hubert H. Humphrey, and Elliot L. Richardson. Includes correspondence (1974 and undated) with Wes Gallagher, general manager of the Associated Press, and congratulatory letters to Pett on winning the Pulitzer Prize for feature writing in 1982.
Motion Picture, Broadcasting and Recorded Sound Division.
Journalist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abourezk, James G., -- 1931-; Carter, Jimmy, -- 1924-; Coleman, William T. -- 1920-; Ford, Gerald R., -- 1913-2006.; Gallagher, Wes, -- 1911- -- Correspondence; Humphrey, Hubert H. -- 1911-1978.; Richardson, Elliot L., -- 1920-1999.; Associated Press; Journalism -- United States; Pulitzer Prizes; Journalists